Understanding Spring Integration : enterprise integration concepts, messaging architecture, techniques for integrating external systems - Bowersox, Kevin; Safari eBooks ([Place of publication not identified] : O'Reilly, 2016)
"Spring Integration is a Java-based tool designed to support information exchange between disparate systems. While APIs may be the standard for information exchange, there is no guarantee they will be the answer to every integration problem. Spring Integration provides a solution to integrating systems that use traditional web services, file transfers, and database sharing to exchange information. Intended for developers comfortable with Java, XML, and the Spring core, this course demonstrates how to leverage Spring Integration's messaging system and external adapters to satisfy the toughest system integration needs."--Resource description page.
Title from title screen (Safari, viewed October 10, 2016).
Date of release from resource description page (Safari, viewed October 10, 2016).
Presenter, Kevin Bowersox.
Keywords: Enterprise application integration (Computer systems); Systems integration; Application software -- Development; Electronic books